Integration of Religious Moderation Values ​​Through Project-Based Islamic Religious Education Learning: A Study on Prospective Teacher Students - Yulianti; Yusuf Hanafi; Nurul Murtadho (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This study aims to identify the urgency of innovation in Project-Based Learning (PjBL) in guiding prospective teachers to have moderate characters. This study uses a qualitative approach with a descriptive method. Data were taken using observation techniques and documentation studies. The data were analyzed in three stages consisting of data reduction, data display and conclusion. The results of the study indicate that innovation in learning models of project-based learning in integrating the values ​​of religious moderation is very important because it can meet the demands of learning that accommodates 21st century competencies, namely communication, collaboration, creativity and critical thinking skills in solving problems. In addition, prospective teachers today require Moral Knowing as a basis in making a decision, including in the context of religious moderation. This study has implications for the importance of innovating in learning to meet the competencies of prospective teachers with moderate characters. Therefore, teachers, lecturers or stakeholders need to continue to encourage project-based learning models through a Moral Knowing approach, especially in integrating moderation values. This research needs to continue to be developed in order to integrate moderate character values ​​in prospective teachers